Ensuring Information Disclosure and Social Involvement in the Siting, Construction and Operation of Civil Nuclear Facilities in China: Legal Challenges and Ways Forward (International Journal of Food and Nutritional Sciences, 2023)
In March 2011, Japan was struck by a massive earthquake that triggered a tsunami, which led to a severe nuclear accident at the Fukushima Daiichi Nuclear Power Plant of the Tokyo Electric Power Company. Now, more than 10 years later, it is widely acknowledged that the civil nuclear industry is of great importance in reducing greenhouse gas emissions, improving natural environmental quality and safeguarding national energy security. Thus, China has been developing its civil nuclear industry throughout the years, despite the nuclear accident in Fukushima, Japan. As a result, China is currently one of the countries with the most nuclear power plants. However, due to the potential radioactive risk, the public has an instinctive fear of civil nuclear development. In order to alleviate the public’s anti-nuclear sentiment, the Nuclear Safety Law was formally implemented in 2018, and Measures for Disclosure of Nuclear Safety Information was issued by the Ministry of Ecology and Environment of China in 2020, both clearly stipulating that the public has the right to obtain information about nuclear safety and be involved in related activities. The purpose of such legislation is to eliminate the public’s doubts and phobia about the development of the civil nuclear industry. However, challenges still exist.